Optical characterization of ALD-coated nanoporous alumina structures: effect of sample geometry or coated layer material - Cuevas, Ana Laura; Vega, Víctor; Domínguez, Antonia; González, Ana Silvia; Prida, Víctor M.; Benavente-Herrera, Juana (MDPI, 2023)
Optical characterization of nanoporous alumina-based structures (NPA-bSs), obtained by ALD deposition of a thin conformal SiO2 layer on two alumina nanosupports with different geometrical parameters (pore size and interpore distance), was performed by two noninvasive and nondestructive techniques such as spectroscopic ellipsometry (SE) and photoluminescence (Ph) spectra. SE measurements allow us to estimate the refraction index and extinction coefficient for the studied samples and their dependence with wavelength for the 250–1700 nm interval, showing the effect of sample geometry and cover-layer material (SiO2, TiO2, or Fe2O3), which significantly affect the oscillatory character of both parameters, as well as changes associated with the light incidence angle, which are attributed to surface impurities and inhomogeneity. Photoluminescence curves exhibit a similar shape independently of sample pore-size/porosity, but they seem to affect intensity values. This analysis shows the potential application of these NPA-bSs platforms to nanophotonics, optical sensing, or biosensing.
Keywords: Oxido de aluminio; Fotoluminiscencia; Propiedades ópticas; Deposición de capa atómica; Alúmina; Nanoporous alumina structures; Ellipsometric spectroscopy; Atomic layer deposition; Photoluminescence; Optical properties